Performance Audit on Tribal Sub Plan Schemes on School Education and Nutrition Components in Tamil Nadu (2011-2014) - CAG of India (CAG of India)
Though allocations were made in Annual Plan Outlays and State Budgets for Tribal Sub Plan (TSP) in proportion to Scheduled Tribe (ST) population of the State, utilisation of TSP funds by Government departments was not optimal and percentage of unutilised TSP funds to budget provisions ranged between 23 and 40. TSP funds provided under the School Education and Nutrition components were not utilised to the extent of 32 to 66 per cent and 28 to 35 per cent respectively. Literacy rate of the State increased from 73.5 per cent in 2001 to 80.1 per cent in 2011 whereas the increase was from 41.5 per cent in 2001 to 54.3 per cent in 2011 in respect of STs. As per 2011 Census figures, 12.5 per cent of 1,32,711 ST children in age group of 7 to 14 years were out-of-school children. Delay in construction of school buildings was noticed in test-checked districts.
For the Period 2011-2014